2018
DOI: 10.2147/idr.s161146
|View full text |Cite
|
Sign up to set email alerts
|

Insertion element mediated <em>mgr</em>B disruption and presence of ISKpn28 in colistin-resistant <em>Klebsiella pneumoniae</em> isolates from Saudi Arabia

Abstract: BackgroundIn Klebsiella pneumoniae, mgrB and components of pmrHFIJKLM operon play a major role in colistin resistance.MethodsWe analyzed 23 nonduplicating colistin-resistant K. pneumoniae isolates, collected during the years 2011–2015, for the possible mechanism underlying their nonsusceptibility to colistin. Isolates were tested for their minimum inhibitory concentrations and antibiotic resistance determinants and genotyped by multilocus sequence typing (MLST). The MLST genes, antibiotic-resistant genes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 19 publications
(26 reference statements)
2
26
2
Order By: Relevance
“…On the other hand, the current rates were even lower than the extremely high rates of cephalosporin and carbapenem resistance among GNPs reported in some developing countries such as Egypt [13], India [29], and Iran [14]. The high rate of resistance in GNPs in the current study is probably reflecting a wide range of resistance mechanisms in GNPs observed in our hospitals, such as NDM, OXA 48 and MGrb and outer membrabe protein (OMP) resistance [30][31][32][33][34]. The high rate of resistance in GNPs in the current study is quite alarming as it already increased the mortality by 25%.…”
Section: Discussioncontrasting
confidence: 63%
“…On the other hand, the current rates were even lower than the extremely high rates of cephalosporin and carbapenem resistance among GNPs reported in some developing countries such as Egypt [13], India [29], and Iran [14]. The high rate of resistance in GNPs in the current study is probably reflecting a wide range of resistance mechanisms in GNPs observed in our hospitals, such as NDM, OXA 48 and MGrb and outer membrabe protein (OMP) resistance [30][31][32][33][34]. The high rate of resistance in GNPs in the current study is quite alarming as it already increased the mortality by 25%.…”
Section: Discussioncontrasting
confidence: 63%
“…The insertion interrupts the coding sequence of mgrB and may contribute to the colistin resistance of KP65. 20 Moreover, a single-base substitution, G169C, leading to the amino acid substitution V57L, was detected in the rpsJ gene. This mutation may contribute to tigecycline resistance in this isolate.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, colistin-resistant Enterobacteriaceae spp. and Acinetobacter spp., in particular A. baumannii, have been identified [16] [17], and infections caused by specific strains of Klebsiellapneumoniae with remarkable resistances to colistin have been recently specified [18]. Pathogenic Gram-negative bacteria with well-known intrinsic resistant to colistin such as Proteus, Serratia, and Morganella have widely isolated [16].…”
Section: Resultsmentioning
confidence: 99%
“…In support, mcr-1 gene-mediated bacterial resistance to colistin has been characterized in several worldwide countries [20], and it was detected not only in infected human samples, but also in foods, animals, and environments [21] [22], reflecting its increased horizontal transfer around the world [23]. In addition to the prevalence of mcr-1 gene, emergence of Klebsiella pneumoniae harboring mutated mgrB-colistin-resistance gene has also been recently raised in Saudi Arabia [18]. Mutations or inactivation in this bacterial gene have previously been identified as the key step in development of bacterial CrrAB and PhoQ/PhoP signaling system mediating colistin resistance [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation